Relationship between anti-thyroid peroxidase antibody positivity and pregnancy-related and fetal outcomes in Euthyroid women: a single-center cohort study - Ning Yuan; Jianbin Sun; Zhi Li; Sanbao Chai; Xiaomei Zhang; Linong Ji (BMC, 2020)
Abstract Background Thyroid autoimmunity (TAI) and subclinical hypothyroidism (SCH) have been associated with poor pregnancy and fetal outcomes. However, whether euthyroid women with anti-thyroid peroxidase antibody (TPOAb) positivity have a higher risk of poor pregnancy and fetal outcomes is debatable. Therefore, this study aimed to investigate the association between TPOAb positivity and pregnancy-related and fetal outcomes in euthyroid women. Methods In total, 938 pregnant women participated in this prospective cohort study. The euthyroid group included 837 pregnant women and the TPOAb-positive group included 101 euthyroid pregnant women. Serum TPOAb, thyroglobulin antibody (TGAb), thyroid-stimulating hormone (TSH), and free thyroxine (FT4) levels were assessed. Pregnancy and fetal outcomes included gestational diabetes mellitus, spontaneous abortion, premature rupture of membranes, hypertensive disorders of pregnancy, preterm birth, fetal distress, low birth weight, fetal macrosomia, and small for gestational age infant. Results Logistic regression analysis showed TPOAb positivity was not associated with an increased risk of poor pregnancy or fetal outcomes in euthyroid women. However, TPOAb-positive euthyroid women pregnant with a female fetus were independently associated with preterm births (OR: 4.511, 95% CI: 1.075-18.926) after adjustment for potential confounding factors. Conclusions TPOAb positivity was not found to be associated with poor pregnancy-related or fetal outcomes in euthyroid women. However, in euthyroid women with a female fetus, TPOAb positivity was strongly associated with preterm births. The risk of preterm birth in the euthyroid women with TPOAb positivity should be emphasized in clinical practice. Trial registration ClinicalTrials.gov Identifier: NCT02966405 . Registered on October 24th 2016 - Retrospectively registered.